A comunicação da ciência nas campanhas de saúde online : um estudo de caso do Portal da Saúde - Berbel, Danilo Brancalhão (Universidade Federal de São Carlos, 2012)
The first registrated public health campaigns in Brazil occurred in the 19th century, when the government created the royal press. In the beginning of 20th century, Oswaldo Cruz s sanitarism s initiatives focused in health campaigns. This approach culminated, sometimes, in insurrection and manifestations. In 1925, the concept of health education brought new perspectives to public approach, intending to change individual behaviors in order to guarantee a healthier life. Later, the concept of health promotion, overcame it, going beyond the goals of providing information and changing behavior: the objective is law proposals and other mechanisms to help people. The history of Brazilian health campaigns is full of faults and skills. A lot of papers have already reviewed these campaigns, but no one investigated the virtual environment provided by the internet in the Brazilian context. The main goal of this research is to investigate how online health campaigns talks to the public, according to the scientific models of communication and to the concepts of health education and health promotion. This paper studies the online campaigns of health alimentation, vaccination and medicines indexed on the Portal da Saúde Brazilian Health Ministry s website. Health education is prevalent in campaigns approach, as the contextual and cognitive deficit models. We conclude that there are a lot of available resources to improve the dialogue to the public, but the online campaigns use communication models to frame medical or scientific authority, providing information and behavior changes. Key-words: health campaigns, online campaigns, models of scientific communication, health education and promotion. ...
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Campanhas de saúde; Campanhas online; Comunicação científica; Educação em saúde; Promoção da saúde; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO::PROCESSOS DA COMUNICACAO